Piezoelectric 1T Phase MoSe2 Nanoflowers and Crystallographically Textured Electrodes for Enhanced Low‐Temperature Zinc‐Ion Storage. Issue 6 (18th December 2022) - Li, Yihui; Dong, Xingfang; Xu, Zewen; Wang, Menglei; Wang, Ruofei; Xie, Juan; Ding, Yangjian; Su, Pengcheng; Jiang, Chengying; Zhang, Xingmin; Wei, Liyu; Li, Jing‐Feng; et al.
Abstract: Transition metal dichalcogenides (TMDs) are regarded as promising cathode materials for zinc‐ion storage owing to their large interlayer spacings. However, their capabilities are still limited by sluggish kinetics and inferior conductivities. In this study, a facile one‐pot solvothermal method is exploited to vertically plant piezoelectric 1T MoSe2 nanoflowers on carbon cloth (CC) to fabricate crystallographically textured electrodes. The self‐built‐in electric field owing to the intrinsic piezoelectricity during the intercalation/deintercalation processes can serve as an additional piezo‐electrochemical coupling accelerator to enhance the migration of Zn 2+ . Moreover, the expanded interlayer distance (9–10 Å), overall high hydrophilicity, and conductivity of the 1T phase MoSe2 also promoted the kinetics. These advantages endow the tailored 1T MoSe2 /CC nanopiezocomposite with feasible Zn 2+ diffusion and desirable electrochemical performances at room and low temperatures. Moreover, 1T MoSe2 /CC‐based quasi‐solid‐state zinc‐ion batteries are constructed to evaluate the potential of the proposed material in low‐temperature flexible energy storage devices. This work expounds the positive effect of intrinsic piezoelectricity of TMDs on Zn 2+ migration and further explores the availabilities of TMDs in low‐temperature wearable energy‐storage devices. Abstract : The piezoelectric 1T MoSe2 /carbon cloth (CC) nanocomposite is fabricated on a crystallographically textured electrode through a facile solvothermal method. The generated piezoelectric field can serve as the zinc‐ion piezo‐electrochemical coupling accelerator to promote kinetics. By virtue of intrinsic piezoelectric effect and phase engineering strategy, this nanopiezocomposite possesses enhanced kinetics and desirable electrochemical performances at low temperatures.